Comparison of sapwood discoloration in fagaceae trees after inoculation with isolates of raffaelea quercivora, Cause of mass mortality of japanese oak trees - Kusumoto,D. (American Phytopathological Society, 2015)
© 2015 The American Phytopathological Society. The mass mortality of oak trees has been prevalent in Japan since the late 1980s. The fungus Raffaelea quercivora is transmitted by an ambrosia beetle, Platypus quercivorus, which causes mortality. The beetle is able to bore galleries into the sapwood of most Fagaceae trees in Japan; however, the level of mortality caused by R. quercivora and P. quercivorus differs greatly among tree species. Previous studies by our research group have demonstrated that the virulence of R. quercivora differs among isolates when inoculated into Quercus serrata logs. However, interactions between the virulence of R. quercivora isolates and the susceptibility of other fagaceous species have yet to be elucidated. In this study, we inoculated the fresh logs of 11 fagaceous species with isolates of low and high virulence, and measured the tangential widths of discolored sapwoods 3 weeks after inoculation. Although the discoloration widths of Q. crispula sapwood were similar among all isolates, those of Q. serrata and Q. acutissima tended to increase with the more virulent isolates. Sapwood discoloration in Q. glauca, Q. acuta, Q. salicina, Lethocarpus edulis, and Castanopsis sieboldii was greatly increased by highly virulent isolates. Discoloration in Fagus japonica was not influenced by any of the isolates. The logs of Q. crispula and Q. serrata but not Q. glauca were significantly more discolored by a low-virulence isolate compared with standing trees. The various virulent isolates induced unique sapwood discoloration characteristics in each species, which may explain species-specific differences in mortality rates.